The Impact of Rapid Growth of Urbanization and Urbanism in Eastern Ethiopia - Shambel Tufa Telila (Journal La Sociale, 2020)
The intention of this paper is to investigate the impact of the rapid growth of urbanization and urbanism in Eastern Ethiopia, challenges and prospects. The researcher used qualitative research approaches and primary and secondary data collection methods that largely include observations, focus group discussion s, interviews. These are the principal methods to look into the etic view of the community under investigation. The paper employs only a qualitative research method to examine the scenario of the impact of rapid urban expansion and challenges and prospects in this study. The empirical studies indicated that the urbanization process causes the dismantling of the immediate rural community and the cause of land grabbing from these societies. Therefore, this study utilizes to study the challenges and prospects of urbanization on the surrounding community immediately adjacent to urban areas. A number of studies indicated that urbanization causes both challenges and prospects in the area where the urbanization process is taking place. Nevertheless, the challenges and prospects of the urbanization on immediate to adjacent communities living in trouble and irritating for their future life. The standard this research finding disclosed that the living condition of the poor urban dwellers and community adjacent to urban areas who were not secured and stable. Even though they got some opportunities such as access to schooling social services markets and access to some important materials for survival. Still, th ese communities are challenged by the alarming rate growth urbanization that evoked impacts on the overall living patterns of these communities.